Assessing the moderating effect of age on the relationship between workability and individual work performance: a study on Malaysian firefighters / Anisah Abas @ Hamdan - Abas @ Hamdan, Anisah (2023)
The ageing workforce phenomenon in most countries, including Malaysia, reflects the high lifespans and rising number of older workers, causing them to live and work longer. In response, the Malaysian government announced the new retirement age in 2012, which has garnered various reactions, as the revision might instigate future complexities involving ageing workers' health, workability (WA), and individual work performance (IWP), specifically for professions requiring physical exertion, like firefighting. Hence, this study aimed to determine the moderating effect of age on the IWP-WA relationship among Malaysian firefighters through systematic and reliable measurement tools, as the impact of age on the relationship remains unaddressed. Based on a pragmatic research philosophy, this cross-sectional study used a mixed-method approach via concurrent triangulation and examined age as a moderator. The results demonstrate a significant relationship between WA-IWP and show that age affects the firefighters' WA in their later age. However, the triangulation result using the permutation test with PLS-MGA analysis and parametric and Weich-Satterthwait tests indicates age does not significantly moderate the WA-TWP relationship, as all the p-values for each test are above 0.05. The findings demonstrate an inverted U-shape relationship between age and job performance among the respondents. In addition, the results are supported and complemented by the qualitative findings. The essence of the transcendental phenomenology approach acknowledges that age affects WA but not IWP. Still, the decline is compensated by individual attributes and factors such as skills, knowledge, and attitude to ensure optimal work quality among firefighters. However, due to the ageing process, the WA is declining, especially in health and function, and may eventually affect the firefighters' IWP in later years.